Impact of endogenous viral elements on glioma clinical phenotypes by inducing OCT4 in the host - Li, Shirong; He, Shuai (Frontiers in Cellular and Infection Microbiology, 2024)
IntroductionEndogenous viral elements (EVEs) are viral sequences integrated within the host genome that can influence gene regulation and tumor development. While EVEs have been implicated in cancer, their role in regulating key transcription factors in glioblastoma (GBM) remains underexplored. This study investigates the relationship between EVEs and the activation of OCT4, a critical transcription factor in GBM progression.MethodsWe utilized CancerHERVdb and HervD Atlas databases to identify potential interactions between EVEs and key genes involved in GBM. Data from 273 GBM patient samples in the TCGA database were analyzed to examine the correlation between OCT4 expression and mutations in glioma-related genes. Furthermore, glioblastoma stem cells (GSCs) were assessed for the expression levels of OCT4 and SOX2, and Pearson correlation analysis was performed.ResultsOur analysis revealed that OCT4 is a pivotal gene activated by EVEs in GBM. OCT4 expression was significantly correlated with mutations in key glioma-associated genes. Higher OCT4 levels were associated with poorer patient prognosis, higher tumor grades, and older age. Additionally, GSCs exhibited elevated expression of both OCT4 and SOX2, with a positive correlation observed between these two genes in GBM patients.DiscussionThis study highlights the potential role of EVEs in driving GBM progression through the activation of OCT4. The findings emphasize the importance of OCT4 in GBM malignancy and suggest that targeting EVE-mediated pathways may provide new therapeutic approaches for GBM treatment.